Gold nanoparticle-based lateral flow immunoassay for the rapid detection of flutriafol residues in food. (2nd February 2023) - Liu, Yang; Liu, Liqiang; Xu, Xinxin; Xu, Chuanlai; Xu, Liguang
Abstract : We developed gold nanoparticle-based lateral flow immunoassay for the rapid detection of flutriafol residues in food, with a visual LOD in rice, tomatoes, and grapes of 0.5 mg kg −1, 0.2 mg kg −1 and 0.5 mg kg −1, respectively. Abstract : As a commonly used crop fungicide with proven adverse effects against various organisms, the excessive use of flutriafol (FTF) has resulted in accumulation of a large amount of residues in crops. In this study, a novel hapten was designed by introducing a long interval arm on its benzene ring allowing sufficient exposure of the FTF active site, for the production of a highly sensitive and specific monoclonal antibody with a half-inhibitory concentration of 1.77 ng mL −1 . Furthermore, for the first time, a gold nanoparticle-based lateral flow immunoassay (LFIA) was developed for the quantitative detection of FTF in foods with a visual limit of detection in rice, tomatoes, and grapes of 0.5 mg kg −1, 0.2 mg kg −1 and 0.5 mg kg −1, respectively, and a cutoff value of 4 mg kg −1, and a calculated limit of detection of 0.045 mg kg −1, 0.035 mg kg −1 and 0.060 mg kg −1, respectively. The recoveries in spiked samples ranged from 90.2% to 110.1% and these results indicated that the gold nanoparticle-based LFIA developed in this study for the rapid detection of FTF in food is a reliable on-site detection method.